The Role of Galectin-3 in Acute Myocardial Infarction: A Narrative Literature Review - Haviz Reddy; Akmal M. Hanif; Taufik Rizkian; Wahyudi (HM Publisher, 2022)
Galectin-3 (Gal-3) is a protein, namely a lectin, that binds to beta galactosides. Gal-3 has been shown to be related to the process of fibrosis, classification of atherosclerosis, and cardiac remodeling. Gal-3 regulation is known to be involved in the process of atherogenesis. Low-density lipoprotein (LDL) Oxidation increases Gal-3 expression in vascular smooth muscle cells. Gal-3 also induces fibroblasts and vascular smooth muscle cells to proliferate and produce fibrosis-related proteins in the extracellular matrix. Inhibition of Gal-3 can reduce the atherosclerotic process and reduce the progression of plaque formation. Gal-3 also induces fibroblasts and vascular smooth muscle cells to proliferate and produce fibrosis-related proteins in the extracellular matrix. Inhibition of Gal-3 can reduce the atherosclerotic process and reduce the progression of plaque formation. Several clinical trials have focused on the role of Gal-3 in acute myocardial infarction patients showing that Gal-3 is upregulated. In these patients. This literature review aims to describe the role of Gal-3 in acute myocardial infarction.